Mechanisms involved in drought stress tolerance triggered by rhizobia strains in wheat - Barquero, Marcia; Poveda, Jorge; Laureano-Marín, Ana M.; Ortiz-Liébana, Noemí; Brañas, Javier; González-Andrés, Fernando (Frontiers in Plant Science, 2022)
Rhizobium spp. is a well-known microbial plant biostimulant in non-legume crops, but little is known about the mechanisms by which rhizobia enhance crop productivity under drought stress. This work analyzed the mechanisms involved in drought stress alleviation exerted by Rhizobium leguminosarum strains in wheat plants under water shortage conditions. Two (LBM1210 and LET4910) of the four R. leguminosarum strains significantly improved the growth parameters (fresh and dry aerial weight, FW and DW, respectively), chlorophyll content, and relative water content (RWC) compared to a non-inoculated control under water stress, providing values similar to or even higher for FW (+4%) and RWC (+2.3%) than the non-inoculated and non-stressed control. Some other biochemical parameters and gene expression explain the observed drought stress alleviation, namely the reduction of MDA, H2O2 (stronger when inoculating with LET4910), and ABA content (stronger when inoculating with LBM1210). In agreement with these results, inoculation with LET4910 downregulated DREB2 and CAT1 genes in plants under water deficiency and upregulated the CYP707A1 gene, while inoculation with LBM1210 strongly upregulated the CYP707A1 gene, which encodes an ABA catabolic enzyme. Conversely, from our results, ethylene metabolism did not seem to be involved in the alleviation of drought stress exerted by the two strains, as the expression of the CTR1 gene was very similar in all treatments and controls. The obtained results regarding the effect of the analyzed strains in alleviating drought stress are very relevant in the present situation of climate change, which negatively influences agricultural production.